Yüksek sanayi bacalarının statik dinamik ve betonarme hesabının bilgisayar destekli tasarım - Gürgen, Vedad (Fen Bilimleri Enstitüsü, 1997)
1950 lerin başlarına kadar sanayi bocalan 50 metreyi geçmeyen nispeten kısa yapılardı ve genellikle tuğladan yapılırlardı. 1950 lerin sonlarına doğru işçi ücretlerinin artışı ile çelik baca imalatı daha ekonomik hale geldi. İlerleyen yıllarda Dünyanın hava kirliliğine karşı daha duyarlı hale gelmesiyle daha yüksek bacaların yapılması gerekti. Bu bacalar 300 metreye kadar olmakla beraber genellikle 80 ile 200 metre arasındaydılar ; bu yükseklikler tuğla için çok fazla çelik için ise ekonomik değildi ve betonarme bacaların imalatına başlandı. Sanayi bacalarının yapımı disiplinler arası bir yaklaşım gerektirir, örneğin; malzeme bilimi, kimya, ısı transferi, akışkanlar mekaniği bilgileri bacaların dizaynında kullanılmaktadır. Dünya üzerindeki hemen hemen bütün bacalar ACI 307 veya DİN 1056 normlarına göre yapılmıştır. 1980 lerin sonlarına kadar bu standartlar betonarme baca hesabı için elastik davranışı ve emniyet gerilmelerini öngörüyorlardı. Bu gerilmeler genelde azdı ve bacanın temele yakın kesitlerinde daha kalın betonarme kesit gerektiriyorlardı. Rüzgar hesabı için Amerika veya Almanyadaki yerel koşullara göre hesap yapılıyor ve dinamik etkiler göz önüne alınmıyordu. 1972 de CICIND in ( Comite International des Cheminees Industrieelles ) kurulmasıyla baca dizaynındaki gelişmeler ivme kazandı, öncelikle emniyet gerilmeleri yönteminden vazgeçilerek taşıma gücü yöntemi kullanılmaya başlandı, rüzgarın dinamik tesiri göz önüne alındı, deprem kuvvetlerinin hesabında dinamik hesap yöntemleri kullanıldı. Bu çalışma kapsamında betonarme sanayi bacasının, elastik hesabı ile taşıma gücü yöntemine göre statik ve dinamik hesabı baca gövdesinden başlayarak temel dahil olmak üzere hesap esasları belirlenerek, bilgisayar programlan geliştirilmiştir. Bunun için genel olarak ACI 1979 ve ACI 1995 standartları esas alınmıştır. Programların etkinliği biri 75 m. diğeri 200 m. yükseklikli iki baca örnek alınarak gösterilmiş ve kullanılan iki yöntem için karşılaştırmalar verilmiştir.

Until the early 1950s, industrial chimneys in the UK were relatively short structures, rarely exceeding 50 m tall and were usually constructed of brickwork, relying on dead weight for stability in high winds. In the later 1950s, as labour costs increased and high quality welded steel become more available, steel chimneys become more economic than brickwork for these relatively short heights. The height of chimneys was usually dictated by the draught requirements of the boiler or furnace served. Power plant chimneys, however, paid more attention to pollution dispersal and tended to be a little taller, being sometimes of concrete and generally sized at 2.5x the height of surrounding buildings. In Germany, it should be noted, brickwork chimneys up to 150 m tall were fairly common at that time. As the world become more concerned about air pollution, chimney heights become usually determined by the need to disperse the flue gases over a wide area, so as to minimise ground level concentrations of pollutants. The resulting chimney heights (up to about 300m but generally between 80 m and 200 m ) were too great for brickwork and steel to be economic, and that situation required the use of reinforced concrete. Concrete chimneys were usually provided with a liner of brickwork, to protect the concrete shell from the hot, aggressive flue gasses. In the 1980s, governments began to respond to environmental concerns and introduced legislation requiring the removal of pollutants from the flue gasses. the major pollutants were usually removed by scrubbing the flue gases with alkaline solutions. This, however, introduced major problems of corrosion. One effect of the new legislation was that the heights of chimneys were no longer necessarily dictated by pollution dispersion requirements. In consequence, very tall chimneys were no longer required and steel chimneys started to become the economic choice ( especially as tall cranes and economic solutions to crosswind oscillation allowed steel chimneys to compete with concrete up to heights of 100 m or so ) One exception was in the Eastern Block, where dispersion continued to be favoured over pollutant removal. As a result, chimneys up to climb in the USSR, where chimneys up to 420 m tall were being built In the 1990s air pollution requirements have become ever more stringent and flue gases from new power stations in Germany are now considered innocuous enough to be released to the atmosphere by way of the water cooling towers, rather then by way of chimneys. Nowadays, fewer and fewer chimneys are being constructed and more attention is being paid to extending the lives of those already in place. The most expensive component of an unplanned chimney repair is usually the cost of lost production from the unit served. XI Looking to the future, it is probable that air pollution requirements will reduce further the pollutants released by chimneys. If we continue to rely mainly on fossil fuels, however, it is difficult to see how the demand to reduce the release of carbon dioxide to the atmosphere can be satisfied. As a result of environmental pressure, there is no doubt that chimneys are not popular with the public. In addition to the normal hazards faced by tall structures, such as foundation settlement and the effects of high winds and earthquakes, chimneys are subject additionally to chemical effects and dynamic and thermal loads, any of which can be critical to their design. During the 1970s, failures caused by these problems precipitated some very expensive lawsuits in the USA and the UK - indeed, one of these cases eventually led to a change in English law. This was the Latent Damage Act of 1986, which a plaintiff can sue to the point at which damage is observed. In order to avoid these situations it is essential that the chimney designer is made fully aware of all operating conditions required of the chimney and, to this end., the CICIND has publised a Customers guide to specifying chimneys. Flue gases contain many chemicals whose type depends on the materials burned. Some of these chemicals may attack structural elements with which they come into contact The most common chemical hazard to a chimney is acid corrosion of vulnerable surfaces, due to the condensation of sulphuric acid from the flue gas. High temperature in the flue gas may be planned and, in these circumstances the chimney design can be arranged to suit. Often, however, damage occurs as a result of an unexpected rise in temperature caused either by fire is unlikely in a chimney serving properly operated boilers. The temperature distribution may not be uniform within the flue gas that the liner in such a chimney is subject to differential temperatures over this length. For most situations, a liner is required to protect the concrete shell from the thermal and chemical effects of the hot flue gases. During the period 1960-1970, liners of diatomaceous clay insulating brickwork, laid in contact with the concrete shell, were popular, but suffered a number of problems. Experience showed that liners of externally insulated acid resistant brickwork, with a ventilated airspace between liner and concrete shell, gave a better performance. Most liners continue to be built of acid resisting brickwork, especially in situations involving flue gas desulphurisation in which the flue gas is cool, wet and highly corrosive. A chimney can have extremely variable operating conditions, which make its design very difficult. Such conditions arise in a chimney serving several furnaces and boilers, or serving a single unit incorporating an energy conservation or pollution scrubbing device capable of being bypassed. In such conditions, a design which suits one situation may be unsuitable for other situations. Such a problem is best solved using a multi flue chimney but where this is not possible compromise is necessary. XII Another difficulty arises when a chimney is required to run for many years without being shut down. Obviously a high degree of reliability must be built into its design together with means of on line inspection and repair. In 1982 two men were killed when a 6 m diameter rainshield became detached from the top of a 150 m tall long chimney in high winds and fell to the ground. Designers should pay attention to the integrity of components attached to chimneys, particularly at the top where the combination of exposure to chemical attack and high winds makes them very vulnerable. Also, corrosion of the outer reinforcement in concrete chimneys can cause spalling. This corrosion is often caused by the downdraught of the flue gases, which condense acid on the outer surface. Even small pieces of spalled concrete can be lethal, when falling 100 m or so. While steel and concrete construction can be designed to resist earthquakes of any intensity and design codes provide rules for this purpose the brittle construction of brickwork liners makes them very vulnerable to damage. It is probably for this reason that Japanese designers have favoured a grouped design for steel chimneys, which permits reasonable economy for heights up to 150 m or so. The complex shape increases wind drag considerably over that of a cylinder, so this type of chimney is usually uncompetitive if no earthquake resistance needed. Most concrete chimneys in the world have been designed using the ACI 307 or DIN 1056 codes. Both of these codes have undergone considerable changes over the years. Until the late 1980s both were written in terms of elastic behaviour and permissible stresses were rather low, which led to fairly thick concrete in the lower part of the chimneys. Wind loads were defined in terms of wind pressure, related to the locality in the US or Germany, and paid no attention to the dynamic response of the chimney. To over come the difficulty of using the codes in other countries, wind loads were usually calculated using local building codes. This of course, introduced some variability in the application of the codes, as wind pressures in local codes were not necessarily determined on the same basis as those in the USA or Germany. This situation come to a head in 1972 when a chimney built in France for a US oil company, was designed using ACI 307. The resulting concrete thickness at the base of the shell was 600 mm, For legal reasons, the design was checked by a French consultant using the French building codes. He found that the required concrete thickness was 200 mm. It was that situation that led to the formation of the CICIND. The CICIND was established with the aim of promoting knowledge about the design, construction and use of chimneys and in particular, to stimulate the harmomsation of national design codes. Since publication of the CICIND Model Code, both DIN 1056 and ACI 307 have been modified to incorporate many of these ideas. While in the 1990s, few new major concrete chimneys have been built, attention has turned to extending the life of existing chimneys. XIII Review of major features of the various codes currently available as follows CICIND. ultimate state design, with safety factors related to failure probability, using sophisticated statistical methods ; the safety factors also take account of the effects of low cycle, high stress fatigue.. recognises that under long term dead loads, concrete behaves in a different manner than when it is subjected to wind loads lasting no more than a few seconds.. wind load expression related to wind velocity and takes account of the chimney's dynamic response to wind gust.. dynamic analysis used to determine the response to earthquakes. reinforcement required in both faces; recognises that thermal stresses are relieved by cracks and provides simple rules to limit the crack widths.. approximations provided for second order effects owning to the deflection of the chimney under ultimate wind loads.. chemical load is defined by hours/year exposure to various chemicals. cross wind response considered. A revision is currently being developed. This will reconsider 1. ( velocity f relationship ( rather than a Gumbel distribution ) to define the ultimate wind velocity 2. effect of ductility on a cocrete chimneys response to earthquakes 3. limits on the use of beam versus shell theory in determining stresses While the first two changes will have the effect of reducing the cost of the chimney shell, the last change could increase the amount of reinforcement in thin chimney shells. xiv ACI 307. Ultimate state design, with safety factors from building code ACI 318 and modified by judgement. Covers precast concrete chimneys in addition to cast in situ chimneys. Wind load expression related to wind velocity and takes account of the chimney's dynamic response to wind gust.. Cross wind response calculated using complex formula. Cross wind and down wind response combined the along wind component being calculated at a reduced windspeed.. Earthquake response calculated using modal analysis.. No rules for chemical effects.. Second order moments accounted for by reducing ultimate strength. DIN 1056 «Covers precast blockwork chimneys as well as reinforced cast in situ concrete.. Ultimate strength design, with safety factors derived by judgement.. Second order moments considered.. Coefficients and limiting stresses defined for calculation of thermal stresses reinforcement required in each face.. Chemical load considered in terms of hours / year of exposure.. Wind pressures defined for various locations in Germany response of the chimney to gusts is considered.. Consideration of cross wind effects only required in exceptional cases no guidance given for a calculating this response..Considers foundation design. The intense studies of the perfonmance and structural design of chimneys and their liners, carried out over 25 years, have shown that, far from being simple structures, they are very complex systems indeed. While sufficient work has been done to xv transform chimney design from the Black Art perceived in the late 1960s, to the science - based procedures of today. In mis thesis both Ultimate strength design and permissible stresses design are used in calculations and earthquake response of the chimney calculated by using modal analysis with various earthquake spectrums and also the overturning momente for the foundation design is calculated, for these overall design purposes, Fortran 77 programs are developed for the tall industrial chimney satisfying the code requirements and fundamental procedures. Examples for the 75 m. and 200 m. chimneys are given using these computer programs and results are also compared for the two methods considering economical purposes.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Bacalar; Bilgisayar destekli tasarım; Chimneys; Computer aided design